Interview with Fábio de Souza Lessa: notes regarding the study of the uses of the body in Antiquity - Lessa, Fábio de Souza (Romanitas - Revista de Estudos Grecolatinos, 2023)
Interview with Fábio de Souza Lessa.
Keywords: Interview; Fábio de Souza Lessa; Body; Antiquity